DESIGNING PUBLIC SERVICE ADVERTISING VIDEOS SELF HARASSMENT WITH MOTION GRAPHIC TECHNIQUES INFOGRAPHIC-BASED AS AN EFFORT TO INCREASE PUBLIC AWARENESS - Rama Dwissa Wiana; Dwika Lutfhi Permana (International Journal of Economy, Education and Entrepreneurship, 2021)
The development of the use of communication and computer technology requires people to be able to filter information and disseminate information that is useful for their social environment. As has happened recently, cases of verbal self-harassment through social media are quite widely discussed in Indonesia. Self harassment discussed is sexual harassment and body shaming. The purpose of this study is to produce a self-harassment public service advertising design with infographic-based motion graphic techniques as an effort to increase public awareness. This study uses a qualitative approach method, with interviews and also direct observation as well as literature studies and also existing studies.  From the results of data collection, a concept was obtained, according to what was studied, namely "morality". This concept aims to make society more moral in acting. The main media is in the form of public service advertising videos with motiongraphic techniques that will discuss starting from explaining what sexual harassment is and also body shaming and the resulting impact to solutions on how to deal with these actions. And also supporting media in the form of flyers, posters, xbanners, stickers and pins